Pengaruh accrual earnings management dan real earnings management terhadap kinerja perusahaan dengan struktur kepemilikan sebagai variabel pemoderasi : Studi empiris - AFRIYENTI, Mayar ([Yogyakarta] : Universitas Gadjah Mada, 2009)
This study intends to test the influence of accrual earnings management and real earnings management on firm’s performance and test the effect of ownership structure in moderating the correlation between accrual earnings management and real earnings management with firm’s performance. A firm that operates accrual or real earnings management apparently presumed to be likely carries out full reports of its well performance operation. Accrual earnings management estimated is with the use of discretionary accrual, while real earnings management measured by adding up the abnormal standardized variables CFO (R_CFO), abnormal production (R_Prod), and abnormal discretionary expense (R_DiscExp). The ownership structure is divided as concentrated ownership structure and spread ownership structure. The sample is non-financial public companies registered at BEI. The number of sample is 118 corporate for 4 years period (2004-2007) This study demonstrates evidence that accrual earnings management does not affect the firm’s performance while real earnings management is affect the firm’s performance. The ownership structure does not affect the correlation between accrual earnings management and firm’s performance, but the ownership structure affecting the correlation between real earnings management and firm’s performance.